Pengembangan Minat dan Bakat Siswa (Studi Kasus Pada Implementasi Kurikulum Merdeka Belajar di SD Negeri 023899 Binjai Timur) - Pulungan, Alfi Syahri; Sulasmi, Emilda (UMSU, 2024)
The purpose of this research is to find out how to develop talents and interests in the study of the implementation of the Independent Learning Curriculum at SD Negeri 023899 East Binjai. The research approach is qualitative, which is descriptive in nature and tends to use analysis. The research respondents were school principals, teachers and students of SD Negeri 023899 East Binjai. Questionnaire, interview, observation, and documentation data collection tools. The results of the research on the development of these students' interests and talents in the implementation of the Independent Curriculum emphasized the development of talents and interests according to the characteristics of the students. So the research for class V students has been prepared, the school feels there is a shortage because students do not develop their talents. Several activities are carried out so that students can carry out activities according to the interests and talents of students properly. Based on the research results, it is known that there is a strong and significant influence between the implementation of developing students' talents and interests at school by distributing questionnaires and providing teachers according to the interests and talents of students at SD Negeri 023899 East Binjai for the 2021/2022 academic year. From the results of the study there were intervals of 20 students whose talent was to participate in scouting, and 35 students who had artistic talent. This means that the better the implementation of developing students' interests and talents at school, the more effective it will be in increasing the implementation of the independent curriculum at SD Negeri 023899 East Binjai.